The Impact of Land Use Change on Groundwater Depth in The Groundwater Transition Zone of Merapi Volcano, Yogyakarta, Indonesia - Sejati, Sadewa Purba; Neritarani, Rivi (Faculty of Geography, Universitas Gadjah Mada, 2024)
Studies of the impact of land use change on groundwater on the southern slopes of Merapi Volcano tend to be carried out on a macro basis. Micro studies, especially in groundwater transition zones, have not been previously conducted. In-depth studies need to be undertaken in the groundwater transition zone on the southern slope of Merapi Volcano to identify the impact of land use change on the dynamics of groundwater depth in 2012-2021. Data was collected through field surveys and remote sensing. Groundwater depth data were collected through field surveys in 2012 and 2021. Groundwater depth data were measured in dug wells. The location of the excavated well was determined by using the systematic random sampling method. Groundwater depth data were analyzed using the kriging spatial interpolation method. The results of groundwater depth interpolation in 2012 and 2021 were then compared to determine the changes. Rainfall data were also used in the study. Rainfall data were collected using remote sensing data through cloud computing. Literature studies related to the condition of monitoring wells were also used to determine groundwater dynamics based on rainfall conditions. Data on land use change for 2012-2021 were collected using remote sensing data. Land use change was analyzed using pansharpening, supervised classification, and overlay methods. Cross-tabulation analysis was performed to determine the impact of land use change on groundwater depth. The groundwater depths in the study area were classified into <6 m, 6-11 m, and >11 m. Changes in land use from irrigated rice fields to settlements and open land to scrub occurred predominantly in the study area. Changes in land use did not have a significant impact on changes in groundwater depth in the study area. Based on cross-tabulation analysis, it is known that 11.46% of the study area experienced groundwater deepening, 7.73% experienced groundwater siltation, and 80.81% experienced no change in groundwater depth in the period of 2012-2021. Groundwater deepening generally occurs in areas dominated by scrub and settlements far from river channels. Groundwater that grows shallower and does not change in depth occurs around irrigated rice fields close to river channels. Land use change that does not significantly impact groundwater depth is likely to occur because rainfall in the study area is high. The aquifer material in the study area also had an excellent ability to drain groundwater coming from the upper slopes of Merapi Volcano.